2016
DOI: 10.1111/anae.13408
|View full text |Cite
|
Sign up to set email alerts
|

Levobupivacaine – dextran mixture for transversus abdominis plane block and rectus sheath block in patients undergoing laparoscopic colectomy: a randomised controlled trial

Abstract: SummaryWe performed a randomised controlled double-blinded study of patients having laparoscopic colectomy with bilateral transversus abdominis plane block plus rectus sheath block, comparing a control group receiving 80 ml levobupivacaine 0.2% in saline with a dextran group receiving 80 ml levobupivacaine 0.2% in 8% low-molecular weight dextran. Twenty-seven patients were studied in each group. The mean (SD) maximum plasma concentration of levobupivacaine in the control group (1410 (322) ng.ml À1) was higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 17 publications
(23 reference statements)
0
20
0
Order By: Relevance
“…TAP blocks provide comparable short-term analgesia to wound infiltration but provide superior analgesia in longer term and in the setting of a multimodal analgesic regimen (Yu et al 2014; Guo et al 2015a). Concerning the choice of local anesthetic, ropivacaine, bupivacaine, and liposomal bupivacaine have all been used in ERPs with good results (Hamada et al 2016; Cohen 2012). Liposomal bupivacaine shows some promise for longer-term postoperative analgesia either as infiltration or for TAP blocks (Hutchins et al 2015); however, there are no large-scale randomized controlled trials available in intra-abdominal surgery to guide practice or to definitively demonstrate the analgesic efficacy of this intervention (Cohen 2012; Candiotti et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…TAP blocks provide comparable short-term analgesia to wound infiltration but provide superior analgesia in longer term and in the setting of a multimodal analgesic regimen (Yu et al 2014; Guo et al 2015a). Concerning the choice of local anesthetic, ropivacaine, bupivacaine, and liposomal bupivacaine have all been used in ERPs with good results (Hamada et al 2016; Cohen 2012). Liposomal bupivacaine shows some promise for longer-term postoperative analgesia either as infiltration or for TAP blocks (Hutchins et al 2015); however, there are no large-scale randomized controlled trials available in intra-abdominal surgery to guide practice or to definitively demonstrate the analgesic efficacy of this intervention (Cohen 2012; Candiotti et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies showed that adding low-molecular weight dextran (LMWD) to LA and an adrenaline mixture reduced systemic adrenaline absorption, abrogating adverse hemodynamic effects [2]. Also, LMWD added to LA induced long-term profound analgesia with lower LA systemic toxicity by reducing systemic LA absorption [3]. These effects were demonstrated in infiltration nerve block (NB) [2], transversus abdominis plane block [3], rectus sheath block [3], quadratus lumborum block [4], and mandibular NB cases.…”
Section: To the Editormentioning
confidence: 99%
“…Also, LMWD added to LA induced long-term profound analgesia with lower LA systemic toxicity by reducing systemic LA absorption [3]. These effects were demonstrated in infiltration nerve block (NB) [2], transversus abdominis plane block [3], rectus sheath block [3], quadratus lumborum block [4], and mandibular NB cases. Formation of an LMWD and LA complex that remains at the NB site longer may be the associated mechanism [3,4].…”
Section: To the Editormentioning
confidence: 99%
“…We did not describe the use of dextran as an LA adjuvant in this review, but it is interesting to extend the LA action using with low-molecular weight dextran. Hamada et al demonstrated that the absorption of levobupivacaine was suppress in 90 min notably adding the 8% lowmolecular weight dextran solution [2]. We hope for high quality postoperative pain management using long acting LA.…”
mentioning
confidence: 90%